Contribution of the indigenous health care givers to the herbal management of febrile illnesses in Rivers state, South-south, Nigeria (2005)
This study was carried out in two rural communities; kaani and Boue, in Khana Local Government Area (LGA) and in one urban community, Elomo, in Elomo LGA, all in Rivers state, South-south, Nigeria. The investigations involved in-depth interview conducted with 104 health care givers comprising indigenous healers: herberlists, sellers of herbal remedies and community elders. Information was obtained on types of fevers (febrile illnesses) treated, symptoms and methods of establishing illnesses, and traditional herbs used in the prevention and treatment of febrile illnesses. On types of febrile illnesses treated, respondents presented the following: malaria (78.8%), typhoid (23.1%), yellow fever (21.2%), high fever (19.2%), convulsion (15.4%), and pregnancy fever (2.9%). Other illnesses treated were yellow eyes (4.8%), headache (11.5%), waist pain (14.4%), and joint pains (8.7%). Respondents determined whether a person had fever by the following: physical examination (85.4%), listening to patients' complaints (9.4%), through divination and inspiration (9.4%), while others (0.2%) were not quite explicit on their methods of diagnosis. On the treatment of febrile illnesees, respondents used herb teas (88.5%), herb powders (42.3%), incantation (3.3%), and performance of sacrifice (4.8%) or use of special fluids (27.9%). Majority of the respondents in describing the best herbal medicines for the treatment of febrile illnesses, 62.5% said that dogonyaro (Azadiracta indica) was the best medicine. Other responses were: lemon grass (Cymbepegon papaya) leaf/fruit (20.2%): guava (Psidium guajava) leaf (18.3%), akpagbogoro (Salacia nitida), 7.7%, plantain (Musa sapientum) sucker (6.7%), lipton tea (3.8%) and scent leaf (Ocimum gratissimum), 1.9%